2022
DOI: 10.3389/fnins.2022.957972
|View full text |Cite
|
Sign up to set email alerts
|

Effects of robot-assisted task-oriented upper limb motor training on neuroplasticity in stroke patients with different degrees of motor dysfunction: A neuroimaging motor evaluation index

Abstract: Introduction: Although robot-assisted task-oriented upper limb (UL) motor training had been shown to be e ective for UL functional rehabilitation after stroke, it did not improve UL motor function more than conventional therapy. Due to the lack of evaluation of neurological indicators, it was di cult to confirm the robot treatment parameters and clinical e cacy in a timely manner. This study aimed to explore the changes in neuroplasticity induced by robot-assisted task-oriented UL motor training in di erent de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…This result is consistent with many longitudinal studies, where the LI in stroke patients tends to increase initially after stroke, then decrease around two months to three months ( 7 ), with some studies showing a significant average decrease in LI at approximately one week after stroke, followed by an increase after three to six months ( 44 ). Some studies have not found enough significant difference in LI ( 11 , 45 ). Similar patterns have been observed for motor evoked potentials (MEPs) and sEMG ( 46 , 47 ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This result is consistent with many longitudinal studies, where the LI in stroke patients tends to increase initially after stroke, then decrease around two months to three months ( 7 ), with some studies showing a significant average decrease in LI at approximately one week after stroke, followed by an increase after three to six months ( 44 ). Some studies have not found enough significant difference in LI ( 11 , 45 ). Similar patterns have been observed for motor evoked potentials (MEPs) and sEMG ( 46 , 47 ).…”
Section: Discussionmentioning
confidence: 97%
“…The fNIRS offers advantages such as non-invasiveness, mobility, resistance to motion and electromagnetic interference, high spatial resolution, and the ability to facilitate long-term monitoring, making it conducive to researching changes in cerebral hemodynamics during muscle contraction tasks ( 7 , 10 ). fNIRS is also increasingly used to assess motor function or motor rehabilitation training effects ( 2 , 11 ). Upper limb motor is the result of the coordination of the nervous system with the corresponding muscles.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have utilized fNIRS to compare cortical activity before and after upper limb training with robotic devices in patients who have experienced a stroke. [11][12][13][14][15] One study conducted robot-assisted therapy in stroke patients with hemiplegia, using fNIRS to compare cortical activity between groups with severe and moderate impairments. [13] However, to the best of our knowledge, few studies are using fNIRS to compare cortical activity after training with a robotic device and conventional device for upper limb rehabilitation in patients with stroke.…”
Section: Discussionmentioning
confidence: 99%
“…[10] Several studies have utilized fNIRS to compare cortical activity before and after upper limb training with robotic devices in patients with stroke. [11][12][13][14][15] However, there is a particular paucity of research comparing the effects of robotic versus conventional devices on cortical activity during upper limb rehabilitation in patients with stroke.…”
Section: Introductionmentioning
confidence: 99%
“…The fNIRS has the advantages of a relatively low price, high time resolution, suitable for more places, and less noise interference. At present, fNIRS is mainly used to observe the changes in cortical activation in subjects under different conditions and after treatment, which strengthens the study of cerebral activity and reveals the principle of cortical remodeling ( 19 ). For example, the fNIRS showed that the asymmetry of sensorimotor cortex activation was significantly improved after 2 months of in-hospital rehabilitation, and the ipsilesional premotor cortex activation increased, suggesting that the motor recovery after stroke may be related to the improvement of sensorimotor cortex (SMC) activation asymmetry and the enhancement of ipsilesional premotor cortex activation ( 15 ).…”
Section: Introductionmentioning
confidence: 99%